Cost‐effectiveness of the introduction of specialized oral care with laser therapy in hematopoietic stem cell transplantation. Issue 1 (29th April 2013) - Bezinelli, Letícia Mello; de, Fernanda; da, Roberta Marques; Biazevic, Maria Gabriela Haye; de, Carlos; Correa, Luciana; Hamerschlak, Nelson; Michel‐Crosato, Edgard
Abstract Oral mucositis (OM) is one of the side effects of hematopoietic stem cell transplantation (HSCT), resulting in major morbidity. The aim of this study was to determine the cost‐effectiveness of the introduction of a specialized oral care program including laser therapy in the care of patients receiving HSCT with regard to morbidity associated with OM. Clinical information was gathered on 167 patients undergoing HSCT and divided according to the presence (n = 91) or absence (n = 76) of laser therapy and oral care. Cost analysis included daily hospital fees, parenteral nutrition (PN) and prescription of opioids. It was observed that the group without laser therapy (group II) showed a higher frequency of severe degrees of OM (relative risk = 16.8, 95% confidence interval −5.8 to 48.9, p < 0.001), with a significant association between this severity and the use of PN (p = 0.001), prescription of opioids (p < 0.001), pain in the oral cavity (p = 0.003) and fever > 37.8°C (p = 0.005). Hospitalization costs in this group were up to 30% higher. The introduction of oral care by a multidisciplinary staff including laser therapy helps reduce morbidity resulting from OM and, consequently, helps minimize hospitalization costs associated with HSCT, even considering therapy costs. Copyright © 2013 John Wiley & Sons, Ltd.